How Knowledge Management Capabilities Help Leverage Knowledge Resources and Strategic Orientation for New Product Advantages in B-to-B High-Technology Firms. Issue 2 (2nd April 2016) - Im, Subin; Vorhies, Douglas W.; Kim, Namwoon; Heiman, Bruce
ABSTRACT: Purpose: Current understanding of how new product development (NPD) teams use knowledge management capabilities to acquire, disseminate, and apply knowledge resources to achieve competitive advantages is limited by a lack of compelling theory supported by empirical evidence. This study provides a theoretical framework and empirical validation for how an NPD team manages knowledge resources and strategic orientation to enhance its knowledge management capabilities, which, in turn, lead to business-to-busienss (B-to-B) new product advantages. Methodology/approach: A total of 100 sets of data was collected from B-to-B firms in U.S. high-tech industries. In order to validate the proposed hypotheses, we estimated the main effects using path analysis in AMOS, and tested for interaction effects using interaction term regressions. Findings: Our findings show that the two dimensions of NPD knowledge management capabilities—acquisition and application—are important but differential drivers of product quality superiority and product differentiation. In testing whether NPD management capabilities matter for two product advantage constructs, we confirmed that product quality superiority can be enhanced by both NPD knowledge acquisition and application capabilities, whereas product differentiation can be increased strongly by NPD knowledge acquisition capabilities. Research implications: Our research confirms the importance of strategic orientation as a driver of NPD knowledge management capabilities, which enhances understanding of how strategic factors operate under a resource-based view. Our results further provide direct empirical support for the knowledge-based view of firms, in that an NPD team's abilities to manage and deploy knowledge-based resources by acquiring and applying NPD knowledge lead to competitive advantages, for outcomes of quality superiority and differentiation. Practical implications: Our findings have relevance for managers in three ways. First, NPD knowledge acquisition and application capabilities have differential impacts on product quality superiority and differentiation. Second, in exploring NPD resource factors as antecedents, managers should manage levels of NPD market intelligence, resource tacitness, and NPD resource deployment differentially to directly improve NPD teams' acquisition and application capabilities. Third, managers should not underestimate the importance of market and technological orientations in enhancing NPD knowledge management capabilities. Market orientation drives both NPD knowledge acquisition and application capabilities; technological orientation drives NPD knowledge application capabilities. Originality/value/contribution of the paper: An NPD team's knowledge management capabilities generally, but differentially, mediate the relationships of knowledge resources and strategic orientation factors with new product competitive advantage. However, simply enhancing NPD knowledge management capabilities is not a panacea for developing product competitive advantage in B-to-B settings, because of their differential effects.